Pelatihan Pembuatan Biobriket Dari Limbah Biomassa Sekam Padi Kelompok Wanita Tani Subur Desa Gondang Kabupaten Lombok Utara - Raehnayati; Tri Wulandari, Febriana; Ningsih, Rima Vera; Sari, Diah Permata; Webliana, Kornelia (Universitas Mataram, 2023)
Scarcity and rising oil prices will continue to occur due to its non-renewable nature. One of the alternative energy sources that is renewable by utilizing biomass waste Indonesia's energy potential from biomass is around 13,662 MWe with an installed capacity of 1,364 MWe in 2014. One of the biomass waste that can be utilized as biobriquette fuel is rice husk. The high potential of rice production in NTB supports the availability of raw materials for rice husk biobriquettes. Several studies related to biobriquettes have been conducted by researchers, including research on biobriquettes from coconut shells, sawdust, bamboo and brown skin. Research related to biobriquettes include: Research related to biobriquettes include: Effect of the Composition of Rice Husk Charcoal and Jatropha Seed Shell Charcoal on the Quality of Charcoal Briquettes, Thermal Characteristics of Rice Husk Charcoal Briquettes with Variations in Adhesive Materials, Determination of Optimum Conditions of Temperature and Carbonization Time in Making Charcoal from Rice Husks. Based on the research that has been conducted, rice husk will be applied into charcoal briquettes (biobriquettes) which can be an alternative fuel that is environmentally friendly and provides financial value for the lower middle class. It is hoped that by providing training in making charcoal briquettes from rice husks this will reduce rice husk waste, provide cheap and environmentally friendly alternative fuels and provide new jobs in the form of business groups so as to get additional income for the community. The objectives of the training activities for making briquettes from rice husk biomass waste are (1). Provide insight to the community about carbonization techniques (charcoal burning) (2). Provide insight into the technique of making biobriquettes, (3). Provide insight into new business opportunities in the community.